Tourism’s impact on human rights: Travel’s best souvenir a case study in Ngwe Saung, Myanmar - E. Pritchard, Ashley (2013)
Key findings from this study indicate that individuals of all ages, occupations and ethnic groups from the Ngwe Saung community experienced a positive increase in sustainable livelihood through increased job opportunity and additional income. Livelihood improvements directly impacted human rights to education, health, hygiene, electricity, transportation, freedom of information and religious opportunity. Results show that tourism development reduced poverty significantly, elevating participants from extreme poverty to a level well above subsistence, unattainable without the jobs and income that tourism generated.